THE IMPACT OF STRATEGIC LEANS IN BUILDING A SMART TOURISM ORGANIZATIONS: AN EXPLORATORY STUDY IN THE TOURISM AUTHORITY (World Bulletin of Management and Law, 2022)
The aim of study To role of role played by strategic lens in building smart tourism organizations(STO) and resulting from intellectual meetings as a result of interactive layout variables of their dimensions (stakeholders, resource mobilization, knowledge development, culture management), variables of (STO) (participation, strategic vision)For sample of leaders in Iraqi tourism body by analyzing chain of leaders of Commission , reality of the60(AGR), (ADM), Director-General, heads of divisions, people's officials) as well as personal interviews with managers in body, information was collected through questionnaire and the researcher was adopted by the transition , provision of statistical interface, the middle-class statistics, the criteria of standard , the multi-registration of a status of statistical means, the most prominent conclusions reached by study of strategy of strategy and the intensive (STO).